EDUCATION QUALITY MANAGEMENT BASED ON HUMAN RESOURCE REVITALIZATION AT MTs AL-MA’ARIF JEMAJA - Madaniyah; Nunu Mahnun (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze education quality management based on human resource (HR) revitalization at MTs Al-Ma’arif Jemaja, Anambas Islands Regency. The main problem addressed in this research is the low quality of education caused by limited teacher competence, inadequate facilities, weak institutional governance, and restricted funding in a remote island context. To address these issues, this study employs a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving the principal, teachers, and foundation board members. The findings reveal that education quality is significantly influenced by the condition of human resources, particularly teachers’ qualifications and professional development. In addition, structural challenges such as limited funding, inadequate infrastructure, and passive foundation management further hinder institutional performance. The study also finds that HR revitalization strategies such as recruiting qualified teachers, providing continuous training, diversifying funding sources, and strengthening foundation governance play a crucial role in improving education quality. These efforts enhance teacher competence, increase motivation, and support better institutional management. In conclusion, integrated and context-based HR revitalization is an effective approach to improving education quality, especially in remote and resource-limited madrasah environments, and can serve as a model for similar institutions facing comparable challenges.